The Good Christian Ruler in the First Millennium : Views from the Wider Mediterranean World in Conversation - Forness, Philip Michael (2021)
This volume brings together historical research on classical antiquity and early medieval Europe with the study of eastern Christianity. To this end, it examines concepts of good rulership, especially of good Christian rulership, to highlight commonalities but also areas of divergence. The wide-ranging specialized studies offer a balanced picture of the cultural diversity of the late antique and early medieval Mediterranean.